2005
DOI: 10.1007/s00213-005-2240-4
|View full text |Cite
|
Sign up to set email alerts
|

5-HT1A receptor expression during memory formation

Abstract: These data suggest that upregulated, downregulated, and "silence" of 5-HT(1A) receptors in brain areas form part of neural circuits engaged in memory formation by demonstrating a high degree of specificity and memory mapping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 22 publications
1
18
0
3
Order By: Relevance
“…It should be noticed that thought in this work no attempt was made to quantify the changes in protein expression following infusions of anisomycin or DRB, the doses and times used are well-known to produce 80-90% of the inhibition of protein and mRNA synthesis and have amnesic effects (see e.g., Davis and Squire, 1984;Izquierdo et al, 2006;Parsons et al, 2006;Alberini, 2008). Notably, that prefrontal protein synthesis mediated STM is in line with evidence that 5-HT 1A , 5-HT 6 , and 5-HT 7 receptors expression (see below) in these brain areas is modified by memory consolidation (Luna-Munguia et al, 2005;. Certainly, though amnesia produced by protein synthesis inhibitors such as anisomycin provides major support for the prevalent view that the formation of long-lasting memories requires de novo protein synthesis, Canal et al (2007) recently suggested that, inhibition of protein synthesis might disrupt other neural functions to interfere with memory formation.…”
Section: Protein and Mrna Synthesissupporting
confidence: 60%
See 1 more Smart Citation
“…It should be noticed that thought in this work no attempt was made to quantify the changes in protein expression following infusions of anisomycin or DRB, the doses and times used are well-known to produce 80-90% of the inhibition of protein and mRNA synthesis and have amnesic effects (see e.g., Davis and Squire, 1984;Izquierdo et al, 2006;Parsons et al, 2006;Alberini, 2008). Notably, that prefrontal protein synthesis mediated STM is in line with evidence that 5-HT 1A , 5-HT 6 , and 5-HT 7 receptors expression (see below) in these brain areas is modified by memory consolidation (Luna-Munguia et al, 2005;. Certainly, though amnesia produced by protein synthesis inhibitors such as anisomycin provides major support for the prevalent view that the formation of long-lasting memories requires de novo protein synthesis, Canal et al (2007) recently suggested that, inhibition of protein synthesis might disrupt other neural functions to interfere with memory formation.…”
Section: Protein and Mrna Synthesissupporting
confidence: 60%
“…Indeed, schizophrenia and 5-HT systems (see Boyer et al, 2007;Millan, 2000, for review) present strong links, mainly in the context of memory formation via hippocampus and medial prefrontal cortex (mPFC) (see e.g., Luna-Munguia et al, 2005;Perez-Garcia et al, 2006). For instance, clinical and preclinical evidence indicates that several new atypical antipsychotic (e.g., clozapine) drugs improve cognition in schizophrenic patients (Millan, 2000;Meltzer and Sumiyoshi, 2003) and memory in animal tasks (see Liy-Salmeron and Meneses, 2007).…”
Section: Introdutionmentioning
confidence: 97%
“…However, the binding sites are increased during memory formation, suggesting the existence of control mechanisms for receptor expression in the GPe (Luna-Munguia et al, 2005). Administration of 5-HT 1A agonists improved movement disorders of Parkinson's disease (Nicholson and Brotchie, 2002;Johnston and Brotchie, 2004).…”
Section: Decrease Of Excitationmentioning
confidence: 99%
“…Although this region appears distinct from a GABA(A) gene cluster implicated in alcoholism (Radel et al, 2005), regions of human chromosome 5q closer to the homologous region of rat chromosome have been implicated in alcohol craving (Ehlers and Wilhelmsen, 2005) and event-related brain potentials in families with a history of alcoholism (Almasy et al, 2001). One of the genes in this region of rat chromosome 2 is that encoding the serotonin 1A receptor, which is expressed in the NAc (Luna-Munguia et al, 2005), couples through Ga i with strongest affinity for Ga i3 (Pucadyil et al, 2005), influences cocaine-induced dopamine levels in the NAc (Andrews et al, 2005) and cocaine-induced locomotion (Carey et al, 2005), and has been implicated in aggressive behaviors, including those induced by cocaine (Knyshevski et al, 2005). A nearby gene is that for tyrosine hydroxylase, the rate-limiting enzyme in dopamine synthesis, which has been implicated in cocaine self-administration (Self et al, 2004).…”
Section: Importance Of Current Findingsmentioning
confidence: 98%